2006
DOI: 10.5664/jcsm.26585
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recalcitrant Restless Legs Syndrome With Botulinum Toxin Type-A

Abstract: Disclosure StatementThis was not an industry supported study. Dr. DiFazio has participated in speaking engagements supported by Alleyum, Inc. Drs. Rotenberg and Cannard have indicated no financial conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…There have been several open-label trials [ 276 , 277 ] and case series [ 278 ] that have studied response of RLS to BoNT. A case series with three patients [ 277 ] and another case series with 27 patients [ 276 ] failed to show improvement of RLS symptoms with BoNT.…”
Section: Discussion Of Bont Use In Different Indicationsmentioning
confidence: 99%
“…There have been several open-label trials [ 276 , 277 ] and case series [ 278 ] that have studied response of RLS to BoNT. A case series with three patients [ 277 ] and another case series with 27 patients [ 276 ] failed to show improvement of RLS symptoms with BoNT.…”
Section: Discussion Of Bont Use In Different Indicationsmentioning
confidence: 99%
“…There was no significant improvement of the IRLS score or clinical global improvement score in the Onabot-A group compared to placebo 99. Two other small open studies (three and eight patients) showed improvement in the control of leg movements with Onabot-A 100,101. Ghorayeb and colleagues,102 in another open-label study, assessed the efficacy of intradermal injection of Abobot-A (250 units to the anterior and posterior thigh muscles) in 26 patients with severe RLS.…”
Section: Use Of Bont For Restless Legs Syndromementioning
confidence: 83%
“…Previous studies assessing the efficacy of botulinum toxins in RLS produced conflicting results. In 2006, Rotenberg [ 21 ] first reported improvement of urge to move legs, nocturnal restlessness, and leg discomfort after injection of Onabotulinumtoxin A (OnaA) into tibialis anterior muscles. In an open label study, eight patients with moderate to severe RLS were injected with OnaA (25 units in each tibialis anterior muscle) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three open label studies and a single, small, randomized double-blind pilot study have evaluated the efficacy of BoNTs in RLS [ 18 , 19 , 20 , 21 ]. These studies demonstrated mixed results with an unclear consensus.…”
Section: Introductionmentioning
confidence: 99%